The Effects Of Labisia Pumila On Postmenopausal Osteoporotic Rat Model: Dose And Time-dependent Micro-CT Analysis. - Nadia Mohd Effendy; Mohd Fadhli Khamis; Ima Nirwana Soelaiman; Ahmad Nazrun Shuid (IOS Press, 2024)
Abstract: BACKGROUND: Postmenopausal osteoporosis is best treated and prevented by estrogen replacement therapy (ERT). Although effective, ERT may cause breast cancer, uterine cancer and cardiovascular problems. Labisia pumila var. alata (LP), a herb with phytoestrogenic, antioxidative and anti-inflammatory effects has potential as an ERT alternative. OBJECTIVE: This study aimed to evaluate micro-CT analysis on the effects of LP supplementation on the trabecular microarchitecture of postmenopausal osteoporosis rat model. Micro-CT is an effective tool in detecting changes in trabecular bone structure and providing a three dimensional information which may replace other conventional bone analysis methods. METHODS: Ninety-six female Sprague-Dawley rats (4 to 5 months old) were randomly divided into six groups of baseline group (BL) Sham-operated (Sham), ovariectomised control (OVXC), ovariectomised with 64.5 μg/kg of Premarin (ERT), ovariectomised with 20 mg/kg of LP (LP20) and ovariectomised with 100 mg/kg of LP at (LP100). The vehicle (deionized water), Premarin and LP were given via daily oral gavages for three, six and nine weeks of treatment periods. Rats in BL group were euthanized before the start of the study, while other rats were euthanized after completion of their treatments. Femora were dissected out and trabecular bone microarchitecture analysed with micro-CT. RESULTS: Micro-CT analysis of OVXC rats revealed significant osteoporotic changes in connectivity density, trabecular bone volume, trabecular thickness, trabecular separation and trabecular number. Both ERT and LP were able to reverse all the OVX-induced bone changes with the best results seen with 100 mg/kg of LP for nine weeks duration of treatment. CONCLUSION: Micro-CT provides accurate and reliable information on trabecular bone parameters which aid in the diagnosis and treatment of osteoporosis. LP supplementation at 100 mg/kg was more effective than ERT in reversing ovariectomy-induced bone changes. Further studies are required to explore the potential of LP as ERT alternative in the treatment and prevention of postmenopausal osteoporosis.